Accommodative Amplitude Before and After Exercise Among Adolescents with Sport-Related Concussion. Issue 5 (31st May 2022) - Storey, Eileen P.; Master, Christina L.; Mannix, Rebekah C.; Haider, Mohammad N.; Meehan, William P.; Willer, Barry S.; Leddy, John J.; Arbogast, Kristy B.; Grady, Matthew F.
Background: Exercise intolerance is a manifestation of autonomic nervous system (ANS) dysfunction after concussion. Accommodative amplitude (AA) may be a useful clinical proxy for ANS dysfunction since accommodation is controlled by the ciliary muscle, which is innervated by parasympathetic fibers of the ANS. Hypothesis/Purpose: To determine if concussion influences autonomic control of accommodative amplitude (AA) by comparing measurements before and after exercise in adolescent sport-related concussion (SRC). Methods: Secondary analysis of data from a randomized controlled trial of aerobic exercise after adolescent SRC. Accommodation was measured before and after the Buffalo Concussion Treadmill Test (BCTT). Fisher's exact tests were used to compare AA before and after exercise, while Wilcoxon rank sum was used to assess the relationship between AA and time until clinical recovery. Results: 99 participants (64.6% male, median age 15.7 (IQR 14.5, 16.8)) had AA measured before and after the BCTT at the initial post-injury visit (median 6 days (IQR 4, 8)). Abnormal AA, defined using Hofstetter's age-adjusted formula, was present in 43 (43.4%) pre-exercise and in 45 (45.5%) post-exercise. Abnormal pre- and post-exercise AA were significantly associated (p < 0.001). AA improved with exercise for 9 participants (i.e., changed from abnormal to normal) while it worsened with exercise for 11 (i.e. normal to abnormal). Low heart rate threshold (HRt), defined as HR less than 135 bpm at test cessation due to symptom exacerbation, was significantly associated with abnormal post- (p = 0.005) but not pre-exercise AA (p = 0.225). Participants with abnormal post-exercise AA had significantly longer time to clinical recovery (median 20.5 days (IQR 14.5, 32)) than those with normal post-exercise AA (median 14 days (IQR 10.75, 21.75)) (p = 0.008). Conclusion: Abnormal post-exercise AA is associated with delayed recovery after SRC. Adolescents with low exercise tolerance are more likely to have abnormal AA after exercise, suggesting that concussion-related autonomic dysfunction is precipitated by an aerobic exercise stress test. Abnormal AA after exercise may provide prognostic utility in concussion.